Differences in crop selection, resource constraints, and crop use values among female- and male-headed smallholder households in Kenya, Tanzania, and Uganda - Reynolds, Travis W.; Tobin, Daniel; Otieno, Gloria; McCracken, Aidan; Guo, Junru (Lyson Center for Civic Agriculture and Food Systems, 2020)
A growing body of research suggests female- and male-headed households in low- and middle-income countries differ in terms of crop choices, access to resources for growing different crops, and values placed on crops for home consumption versus market sale. To better understand relationships between gender of the household head, household resources, individual values, and crop choices, we draw on original survey data collected from 1,001 rural households in Kenya, Tanzania, and Uganda. Bivariate and multivariate analyses suggest that female-headed households are less likely to grow cash crops, reflecting a combination of resource constraints and social norms. However, on average, female-headed households plant more diverse food crops per hectare of land to which they have access, consistent with past findings suggesting crop diversity is a strategy employed by resource-constrained female-headed households to meet household food security needs. We also find that women surveyed on behalf of their households place a higher value on crops for food security, while men more frequently emphasize income potential. These results provide novel cross-country evidence on how female- and male-headed households, and women and men farmers within households, may prefer different crops and also face different levels of access to resources needed for market-oriented agriculture. Such findings support recent calls for development practitioners to carefully consider how market-oriented programs and policies may differentially affect female- and male-headed households and individuals residing within them. We also underscore the importance of collecting gender-disaggregated data to capture meaningful differences in preferences and constraints across women and men at the inter- and intra-household level.